Beyond the usual: Scrotal liposarcoma with skeletal metastasis (Indian Journal of Case Reports, 2025)
Paratesticular liposarcomas, particularly those arising from the spermatic cord, are rare, and dedifferentiated liposarcomas (DDLPS) in this location are even more uncommon. We report the rare case of a 60-year-old male presenting with progressive back pain and scrotal swelling. Imaging revealed a scrotal soft tissue mass and lytic vertebral lesion. The patient underwent wide local excision of the mass. Histopathological examination confirmed high-grade DDLPS, and immunohistochemistry showed strong positivity for CDK4 and MDM2, with patchy positivity for smooth muscle actin and desmin. Whole-body positron emission tomography-computed tomography revealed suspicious lesions in the spine and inguinal lymph nodes. Spinal biopsy was initially negative, subsequent disease progression confirmed vertebral metastases. The patient received systemic chemotherapy (gemcitabine–docetaxel), followed by pazopanib and palliative radiotherapy to spinal lesions. This case highlights the diagnostic and therapeutic challenges associated with paratesticular DDLPS. Although metastases are uncommon in DDLPS, bone involvement, as seen in this patient, indicates an aggressive disease course. Despite standard therapies, the prognosis in metastatic cases remains guarded, underscoring the need for newer targeted options.